Maintenance treatment with chemotherapy and immunotherapy in non-small cell lung cancer: a case report - Llanos, Anabella; Savignano, Mariana; Cinat, Gabriela (Frontiers in Oncology, 2012)
A 53-year-old woman was diagnosed with lung adenocarcinoma state IV (synchronous pleural involvement) in April 2009. First-line systemic treatment included 6 cycles of Carboplatin, Paclitaxel, and Bevacizumab. Partial response was achieved. Maintenance therapy with Bevacizumab and Pemetrexed was given from September 2009 to February 2010. No response changes were observed. Immunotherapy was initiated, and then Pemetrexed was given with the same disease status. Both treatments were well tolerated. Immunotherapy toxicity included reaction at the site of injection grade 2. At present, the patient is still on this treatment. Given the poor prognosis of patients with advanced lung cancer, the combination of both treatments during the stable phase of the disease may improve progression-free survival.